2016
DOI: 10.3844/ajassp.2016.924.931
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Efficacy of Antiretroviral Treatment in HIV Patients: Case of Dr George Mukhari Academic Hospital in Tshwane, Gauteng Province, South Africa

Abstract: This paper used survival analysis to evaluate the efficacy of antiretroviral (ARV) treatment in HIV patients and also to determine if ARVs reduces the risk of HIV/AIDS. Secondary data were collected from files archived in Tshepang Clinic in Dr George Mukhari Academic Hospital in Tshwane, Gauteng Province of South Africa. Survival time was regressed on influential variables that affect survival. The statistical data analysis was conducted using STATA. Both descriptive and inferential statistics were used in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…6,7,9 Antibiotic choice: Orthopaedic SAP choice was deemed correct if a cephalosporin such as cefazolin, cefuroxime or ceftriaxone was prescribed with vancomycin, teicoplanin or clindamycin as indicated alternatives due to cephalosporin allergy or suspected methicillin-resistant Staphylococcus aureus (MRSA) infection. 6,9,13 Route of administration: Antibiotics indicated for orthopaedic SAP use should be administered intravenously (IV).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…6,7,9 Antibiotic choice: Orthopaedic SAP choice was deemed correct if a cephalosporin such as cefazolin, cefuroxime or ceftriaxone was prescribed with vancomycin, teicoplanin or clindamycin as indicated alternatives due to cephalosporin allergy or suspected methicillin-resistant Staphylococcus aureus (MRSA) infection. 6,9,13 Route of administration: Antibiotics indicated for orthopaedic SAP use should be administered intravenously (IV).…”
Section: Methodsmentioning
confidence: 99%
“…9 A study conducted at a Gauteng hospital revealed a 29% compliance rate with SAP dosing recommendations among eight different surgical disciplines. 13 Furthermore, an unnecessarily prolonged duration of SAP was observed in 66% of the cases. 13 A study conducted in a private hospital in KwaZulu-Natal found that only 39.5% of antibiotics prescribed for SAP in general reflected the recommended antibiotic choice, dose and duration.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation